Methods of Fine Motor Development in 5-6 Year Old Children at TK Tunas Cahaya Kubu Raya - Dira Arthamevia Agustina; Dian Miranda; Lukmanulhakim (Journal of Early Childhood Development and Education, 2024)
This research aims to describe how Tunas Cahaya Kubu Raya Kindergarten teachers help children aged five to six years develop their fine motor skills.This research method uses descriptive qualitative. The subjects of this research were the head of the kindergarten and the Group B teacher at the Tunas Cahaya Kubu Raya Kindergarten. The data collection techniques used in this research are interviews, observation and documentation. Data analysis carried out data collection, data reduction, data presentation, and drawing conclusions. The technique for checking data validity is triangulation. The findings of the study demonstrate: 1. How to use resources, media, and procedures to support children's fine motor skill development while they carry out learning activities in order to ensure their success. The technique of assigning homework that helps kids improve their fine motor abilities is to provide them solo and group tasks that test their skills. Play techniques: Individual and group play activities using media and instruments like plasticine, ring cones, balls, etc. help kids improve their fine motor abilities. A learning activity carried out by teachers to develop fine motor skills in children aged 5-6 years. The suggestions in this research are that in delivering the material teachers use words that are easy for children to understand and that teachers can give tasks to children that can be done at home so that children's fine motor development can develop optimally.